2006
DOI: 10.1128/jvi.00180-06
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Activity of Epstein-Barr Virus Latent Membrane Protein 1 (LMP-1) Is Down-Regulated by Lytic LMP-1

Abstract: The Epstein-Barr virus (EBV) is an oncogenic human herpesvirus. EBV latent membrane protein 1 (LMP-1) is a viral oncogene that manifests its oncogenic phenotype through activation of cellular signaling pathways involved in cell growth, survival, differentiation, and transformation. Lytic LMP-1 (lyLMP-1) is a related EBV gene without oncogenic properties. The lyLMP-1 gene is found in 60% of the EBV strains circulating in nature, but it is not found in EBV strains associated with nasopharyngeal carcinoma. We rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…lyLMP1, has 258 amino acid residues ~42-kD, expressed in the lytic phase (43). Modulation of LMP1-activated signaling pathways was the first identified biological activity associated with lyLMP1, and this activity may contribute to the progression of EBV's lytic cycle (43,44). The present findings also suggested that LMP1 and lyLM1 were expressed in B95-8 and CNE1-LMP1 cells and that there was spontaneous reactivation of EBV in the cell lines.…”
Section: Discussionsupporting
confidence: 54%
“…lyLMP1, has 258 amino acid residues ~42-kD, expressed in the lytic phase (43). Modulation of LMP1-activated signaling pathways was the first identified biological activity associated with lyLMP1, and this activity may contribute to the progression of EBV's lytic cycle (43,44). The present findings also suggested that LMP1 and lyLM1 were expressed in B95-8 and CNE1-LMP1 cells and that there was spontaneous reactivation of EBV in the cell lines.…”
Section: Discussionsupporting
confidence: 54%
“…S4). LyLMP1 does not activate NF-κB signaling itself and in fact appears to counteract (latent FL) LMP1 signaling [59], [60]. Whereas during latency LMP1 provides proliferative and survival signals through NF-κB, lyLMP1 could cooperate with BPLF1 to reduce NF-κB activation in B cells producing new virions.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of the LMP1 5Ј regulatory region has been noted in NPCs with undetectable LMP1 expression (22,23). The expression of lytic LMP1 has been proposed as a posttranslational regulatory mechanism (24). However, the promoter that drives the lytic form of LMP1 protein is consistently absent from EBV strains isolated from NPC.…”
Section: Discussionmentioning
confidence: 99%